The effects of lower-extremity plyometric training on soccer-specific outcomes in adult male soccer players: A systematic review and meta-analysis - van de Hoef, P. A.; Brauers, J. J.; van Smeden, M.; Backx, F. J. G.; Brink, M. S. (International Journal of Sports Physiology and Performance, 2020)
Background: Plyometric training is a specific form of strength training that is used to improve the physical performance of athletes. An overview of the effects of plyometric training on soccer-specific outcomes in adult male soccer players is not available yet. Purpose: To systematically review and meta-analyze the effects of plyometric training on soccer-specific outcome measures in adult male soccer players and to identify which programs are most effective. Methods: PubMed, Embase/Medline, Cochrane, PEDro, and Scopus were searched. Extensive quality and risk of bias assessments were performed using the Cochrane ROBINS 2.0 for randomized trials. A random effects meta-analysis was performed using Cochrane Review Manager 5.3. Results: Seventeen randomized trials were included in the meta-analysis. The impact of plyometric training on strength, jump height, sprint speed, agility, and endurance was assessed. Only jump height, 20-m sprint speed, and endurance were significantly improved by plyometric training in soccer players. Results of the risk of bias assessment of the included studies resulted in overall scores of some concerns for risk of bias and high risk of bias. Conclusion: This review and meta-analysis showed that plyometric training improved jump height, 20-m sprint speed, and endurance, but not strength, sprint speed over other distances, or agility in male adult soccer players. However, the low quality of the included studies and substantial heterogeneity means that results need to be interpreted with caution. Future high-quality research should indicate whether or not plyometric training can be used to improve soccer-specific outcomes and thereby enhance performance.